Wood inhabiting fungi (Agaricomycetes) new for India - Sanyal, Sanjeev Kumar (Mushroom Research, 2022)
This paper is focused on the descriptions of twenty four agaricomyceteous fungal species which have been recorded for the first time from different regions of India. The paper includes the taxonomic descriptions, distribution and identification key of the species. Also the previous reports of these fungi from other parts of the world have been included.